Educational robots for children with autism spectrum disorders. (15th March 2023) - Gkiolnta, Eleni; Syriopoulou-Delli, Christine K.
Play is an essential activity for all children and it is linked with the development of many aspects of their social skills. Despite gaining satisfaction, children with ASD face problems when engaging in different types of play. The current review focuses on the use of educational robots that can work as mediators for play activities for children with ASD. More specifically, the enhancement of play skills for school-aged children with ASD through robotics was evaluated through a selection of five eligible studies. The methodology was structured in five steps and followed corresponding methodology criteria. Results indicated that different types of educational robots that were employed in the selected studies were successful in enhancing play skills in general, and more specifically, collaborative play skills in school-aged children with autism, which engaged in interactions with typically developing peers and/or adults. In addition, many aspects of their social skills were improved, such as their joint attention, verbal communication, imitation, and others. Overall, although results were encouraging, there were certain points of attention which needed to be discussed and specific parameters that should be taken into account when designing such interventions, such as the need for customisation and evaluation of children's needs.